Opportunities and strategic use of agribusiness information systems - Che, Ferdinand Ndifor, 1967-; Strang, Kenneth David, 1962-; Vajjhala, Narasimha, 1978- (Advances in business information systems and analytics (ABISA) book series., 2021)
"Agricultural stakeholders in developing countries, particularly in Africa, have not been able to reap comparable benefits from adopting agricultural information systems compared to their counterparts in the developed economies. This book gives solutions to the problems in Africa and other developing countries and provide research findings to help stakeholders overcome the problems that hinder the effective adoption of agricultural information systems"--